FAKTOR-FAKTOR YANG MEMPENGARUHI LITERASI FINANSIAL MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS BRAWIJAYA - Irin Widyawati (Assets: Jurnal Akuntansi dan Pendidikan, 2012)
The purpose of this study to clarify: (1) the influence of socio-economic status of parents towards education family financial management, (2) the influence of parental socioeconomic status on cognitive aspects of financial literacy, (3) the influence of parental socioeconomic status on financial literacy aspects of attitude, (4) the effect of family financial management education to the cognitive aspects of financial literacy, (5) the effect of family financial management education for financial literacy aspect of attitude, (6) the effect of learning in higher education to cognitive aspects of financial literacy, (7) the effect of learning college for financial literacy aspect of attitude; (8) the effect of socioeconomic status of parents of student cognitive aspects of financial literacy through education family financial management; (9) the influence of socio-economic status of parents towards financial literacy aspect of student attitudes through education family financial management . Data collected using tests and questionnaires from 220 students. Data analysis techniques in this study using path analysis. The results of the study are: (1) socio-economic status of parents significant positive direct effect on education family financial management, (2) socio-economic status of parents does not directly influence the cognitive aspects of financial literacy, (3) socio-economic status of parents do not have direct the financial literacy aspect of attitude, (4) education family financial management a significant positive direct effect on the cognitive aspects of financial literacy, (5) education family financial management a significant positive direct effect on financial literacy aspect of attitude, (6) learning in higher education have direct positive significant impact on the cognitive aspects of financial literacy, (7) learning in higher education have significant positive direct effect on financial literacy aspect of attitude; (8) socio-economic status of parents significantly positive indirect effect on the cognitive aspects of financial literacy education mediated by family financial management; (9) the socioeconomic status of parents significantly positive indirect effect on the financial literacy aspect of attitude that is mediated by a family financial management education.